PENGARUH SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN, PEMAHAMAN BASIS AKRUAL TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH - Kiranayanti, Ida Ayu Enny; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
This study aims to determine the effect of the competence of human resources, internal control systems and an understanding of the regulation of government accounting system based akrualterhadap quality of local government financial reports Badung. The approach used in this study is the quantitative approach. Data used in this study are primary data and secondary data. Questionnaire submitted to the 108 employees of the District SKPD delinquent who works in accounting / finance, as many as 108 questionnaires (100%) again filled with lengakap and can be processed. The data collected were processed using SPSS software program. The statistical method used to test the hypothesis is multiple linear regression analysis. The results showed that the competence of human resources, internal control systems, and an understanding of the regulation of accrual-based accounting system of government has a positive and significant impact on the quality of local government financial reports.
Keywords: Quality of Financial Reports, Competence Human Resources, Internal Control Systems, Understanding Upper Regulation Accrual Based Government Accounting System